Time error in perception of sound brightness - Tomasz ŁĘTOWSKI; Jacek SMURZYŃSKI (Archives of Acoustics, 2016)
The paper presents the results of experiments in perception of sound brightness. The purpose of the investigation was to define paired comparison conditions in which the time error (TE) occurs. The duration of the interstimulus interval (ISI) between two white noise signals was used as an independent variable. No TE was observed for ISI of 0.1-2 s. A small negative TE occurred for longer ISI (4-8 s). Similar results were obtained for the noise stimuli limited in the low and high frequency range.